The expansion of giant liver fluke (Fascioloides magna) in southwestern Hungary –Preliminary article - Halász, Tibor; Nagy, Gábor; Csányi, Erika; Németh, Sándor; Csivincsik, Ágnes (Acta Agraria Kaposváriensis, 2020)
The giant liver fluke Fascioloides magna has several continuously expanding natural endemics (northern Italy, the eastern region of Midle-Europe, mainly connected to the Danube (Austria, Slovakia, Hungary, Croatia, Serbia), and the connecting region of Germany, Czech Republic and Poland) in Europe. The giant liver fluke has an indirect life cycle, wherein mainly the red deer and fallow deer role as final hosts. To our present knowledge, in the European habitats, just three species (Galba truncatula, Radix peregra, Radix labiata) belonging to Lymnaeidae amphibian snails could be naturally infected and serve as the intermediate hosts of F. magna. The spread of the fluke is caused by the migration and transportation of infected definitive and intermediate hosts. This study is a part of a systematic regional monitoring programme with the aim of investigating different habitats within the southwestern part of Hungary to confirm the presence and spread of F. magna. In the study, the results of five shot red deer are presented. The livers went through with a thorough post-mortem examination. Isolated flukes were identified by morphological and molecular methods. In four cases, some worm specimens were detected; while in a male yearling, just marked pathological changes were observed in its liver. The morphology and the molecular diagnostic tests verified F. magna infection. The distances between the known northernmost presence in Inner-Somogy and the present shooting points were ranged from 21.0 km to 37.8 km. These results showed a similar pattern as it was observed in other habitats around river Drava. Based on the distance data, the authors concluded that the worm is extending from South to North in the southwestern part of Hungary. Despite the habitat characterisation, viz lack of considerable constant water flows (rivers, creeks, ditches); it seems the high red deer density and the capable wet habitat patches, where the intermediate host could exist, may provide the continuous spread of F. magna.
Keywords: American liverwort; Fascioloides magna; Southern Transdanubia; Red Deer (Cervus elaphus)